Anal Sphincter Anatomy Prepregnancy to Postdelivery Among the Same Primiparous Women on Dynamic Magnetic Resonance Imaging. Issue 1 (January 2019) - Meriwether, Kate V.; Lockhart, Mark E.; Meyer, Isuzu; Richter, Holly E.
Abstract : Objectives: The authors used 2-dimensional images from pelvic 3 T magnetic resonance imaging (MRI) to characterize changes in the internal anal sphincter (IAS) and external anal sphincter (EAS) from prepregnancy to postdelivery in the same cohort. Methods: This secondary analysis studied a prospective cohort of women undergoing 3 T MRI before their first pregnancy and 6 or more months after delivery. Radial thickness was measured at 12, 3, 9, and 6 o'clock from axial proximal and mid views and oblique distal views of the IAS, and at 3 and 9 o'clock from oblique views of the EAS. Measurements were compared prepregnancy to postdelivery; 10 women had 80% power ( α = 0.05) to detect a 0.85-mm change. Results: Nineteen women completed initial 3 T MRI, 15 achieved pregnancy and birth, and 10 completed postdelivery MRI (4 vaginal birth and 6 Cesarean delivery). Mean change in measurement from prepregnancy to postdelivery was −0.01 mm ± 1.03 mm for the distal 12 o'clock IAS ( P = 0.98) and +0.19 ± 0.64 mm for the lateral EAS ( P = 0.32). All prepregnancy and postdelivery women had discontinuous EA sphincters at 6 and 12 o'clock. There were no statistically significant changes from prepregnancy to postdelivery in any IAS or EAS location (all >0.05) for the entire cohort, those with vaginal birth, or after Cesarean. Conclusions: Anal sphincter measurements on MRI did not change significantly in nulliparous women prepregnancy to postdelivery at any location, and the EAS was not measurable at 12 o'clock in any women at either time point, challenging classic concepts of EAS anatomy. Abstract : MRI anal sphincter measurements don't alter significantly from pre-pregnancy to postpartum in the same cohort, the 12 o'clock external sphincter is not measurable either time point.